Normativitas dan historitas Islam dalam pendidikan pesantren: Menjaga tradisi di era modern - Novianti, Nabila Putri; Jifani, Rizkiyan Delikia; Ramadhani, Hanifah; Abbadi, Moh; Ghozi, Ahmad (Maliki Interdisciplinary Journal, 2024)
Islamic education in Indonesia plays a crucial role in preserving and disseminating Islamic teachings. This article examines how pesantrens maintain Islamic normativity and historicity amidst the challenges of modernization. Normativity refers to the consistent application of Islamic values and laws, while historicity pertains to the preservation of traditions and customs handed down through generations. This study employs a qualitative approach with case study methods at several pesantrens in Java and Sumatra. Data was collected through document analysis. The findings reveal that pesantrens have successfully integrated religious education with modern science without losing their traditional identity and values. Strategies employed include curriculum adaptation, the use of technology in classrooms, and the development of entrepreneurship programs. However, challenges such as secularization and globalization still require ongoing attention and strategies to ensure that pesantrens continue to serve as the moral and intellectual centers of Islam in Indonesia.